Analisis Kualitas Jejak Karbon Akibat Penambahan Bangunan Gedung di Pondok Pesantren Miftahun Najah Muaro Jambi - Herawati, Peppy; Adriansyah, Endi; Marhadi, Marhadi; Fadli, Muhamad (Universitas Batanghari Jambi, 2024)
The contribution to the increase in CO2 emissions can come from all the activities of construction workers who use energy such as the procurement of building materials, the use of transportation fuels, the activity of using electricity, and the activity of using LPG. The carbon footprint is a measure of the total amount of carbon dioxide (CO2) emissions originating from activities or the accumulation of daily activities. carbon footprint calculation using the IPCC 2006 method. The carbon footprint calculation results obtained from the development activities of the Miftahun Najah Islamic boarding school building in the procurement of building materials resulted in a carbon footprint of 2.8417 tons. CO2-eq, trucking activities, construction workers produced 550.7 tons. CO2-eq, the activity of using electricity produces a carbon footprint of 39.403 ton.CO2-eq/kWh, and the activity of using LPG produces a carbon footprint of 0.11 ton.CO2-eq. The purpose of measuring the quality of Carbon Dioxide (CO2) is to determine the concentration of CO2 during the development of buildings at the Miftahun Najah Islamic Boarding School.